Efektivitas Model Riset Berdampak dalam Menyelesaikan Permasalahan Sosial Ekonomi di Provinsi Jambi - Deka Veronica; Adi Putra; Candra Ovita Sari (Universitas Batanghari Jambi, 2026)
This study aims to examine the effect of implementing an impact-oriented research model by lecturers at Universitas Muhammadiyah Jambi on the resolution of local issues in Jambi Province, with local stakeholder support acting as a mediating variable. Data were collected through questionnaires administered to 42 lecturers and analyzed using path analysis. The results indicate that the impact-oriented research model has a strong direct effect on resolving local issues, with a coefficient of 0.587. An indirect effect of 0.074 was also identified through local stakeholder support. The total effect of 0.661 suggests that stakeholder support functions as a partial mediator. These findings highlight the importance of strengthening impact-oriented research to enhance the relevance, usefulness, and sustainability of university research.